Guidelines for Open Educational Resources (OER) in Higher Education - United Nations Educational, Scientifi and Cultural Organization (United Nations Educational, Scientifi and Cultural Organization, 2017)
Tài liệu hướng dẫn về tài nguyên Giáo dục Mở (OER) trong Giáo dục Đại học